Cutibacterium modestum sp. nov., isolated from meibum of human meibomian glands, and emended descriptions of Cutibacterium granulosum and Cutibacterium namnetense. Issue 4 (19th April 2020) - Dekio, Itaru; Sakamoto, Mitsuo; Suzuki, Tomo; Yuki, Masahiro; Kinoshita, Shigeru; Murakami, Yoshiyuki; Ohkuma, Moriya
Abstract : An anaerobic and aerotolerant bacterium, strain M12 T, was isolated from the meibum of inflamed human meibomian glands. Cells of the strain was Gram-stain-positive, non-spore-forming and non-motile rods. Growth on trypticase soy agar plates supplemented with 5 % sheep blood was fastest at 30–37 °C under anaerobic conditions. The 16S rRNA gene sequence of the strain revealed that it belongs to the genus Cutibacterium with a 98.0 % similarity value to the closest species, Cutibacterium acnes . Genome analysis of the strain with type strains of the other Cutibacterium species resulted in digital DNA–DNA hybridization values of 32.3–22.3% and average nucleotide identity (OrthoANI) values of 86.7–73.6 %. Biochemical and physiological analyses using API rapid ID 32A and API Coryne kits revealed relatively low reactivity of the strain compared with C. acnes and Cutibacterium namnetense . The most abundant major cellular fatty acid was iso-C15 : 0 . Fermentation end-products from glucose were propionate, lactate, succinate and acetate. The diagnostic diamino acid of the peptidoglycan was meso- diaminopimelic acid. Major menaquinones were MK-9(H4 ), MK-9(H2 ) and MK-9. The major peaks of the MALDI-TOF mass spectrometry spectrum were at 3493, 3712, 6986 and 7424 Da. The DNA G+C content was 59.9 mol%. Based on these findings, we propose a novel species, Cutibacterium modestum . The type strain of C. modestum is M12 T (=JCM 33380 T =DSM 109769 T ). On the basis of further genomic analysis, we also provide emended descriptions of Cutibacterium granulosum (Prévot 1938) Scholz and Kilian 2016 and Cutibacterium namnetense (Aubin et al . 2016) Nouioui et al. 2018.